ANALISIS PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Yudistira, Eka Maisa; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to determine the effect of working capital management proxied by Cash Conversion Cycle, Account Receivable Period, Account Payable Period, and Inventory Conversion Period on profitability in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in Indonesia. Profitability is proxied by Return On Assets (ROA) as a measure of a company's ability to earn profits from the use of all of its resources or assets. This study uses secondary data obtained from annual reports of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The number of samples used was 59 taken by purposive sample method. The results of this study indicate that the cash conversion cycle has a negative and significant effect on profitability, the account receivable period has a positive and significant effect on profitability, and the account payable period has a significant negative effect on profitability. Meanwhile, the results for the inventory conversion period show that there is no significant effect on profitability.